Eisenia arborea (Areschoung) domestication and mariculture development on the Pacific coast of Baja California, México - Zertuche-González, José A.; Sandoval-Gil, Jose M.; Sánchez-Barredo, Mariana; Altamirano-Gómez, Zarko; Guzmán-Calderón, José M.; Rangel-Mendoza, Laura K.; Ladah, Lydia B.; Cruz-López, Ricardo; Yarish, Charles (Frontiers in Marine Science, 2022)
Eisenia arborea (sensu Ecklonia arborea) is the kelp with the greatest latitudinal distribution on the Northeastern Pacific Coast. It is harvested in Mexico in small amounts for abalone farm fodder and occasionally exported to Asia for human consumption. Because the high-energy environment where it naturally grows limits its sustainable harvest, we explored the domestication and cultivation of this kelp on the west coast of Baja California, Mexico. The life history of E. arborea was completed in the laboratory following traditional methods for kelp cultivation. Gametophytes became reproductive approximately 50 days after spore release and sporophytes were visible to the naked eye after 80 days. When sporophytes reached 2–3 cm, they were transplanted to two sites on long-line systems: in an open bay (Todos Santos Bay) and in a shallow coastal lagoon (San Quintín Bay). At both sites, full differentiation occurred 6 to 8 months after deployment, with fertile blades occurring within a year. Once individuals reached maximum size, blades were harvested by pruning. Monthly, regrowth of pruned blades and new blade addition were measured. Pruned individuals reached the same weight as controls in three months. On the basis of these results, a seasonal seeding program was implemented at a third site where the presence of natural Eisenia is rare due to the lack of hard substrate but was hypothesized to provide appropriate conditions for kelp cultivation (Santa María Bay). Cultures were deployed at three different depths and growth was correlated with season, depth, and temperature. Only cultures seeded in winter developed successfully at this site. This study shows that the culture of E. arborea in a variety of ocean conditions is possible; however, site selection and seasonality are important considerations. Because E. arborea is perennial, it can be harvested periodically during the year thereby increasing yield, and because it is the warmest tolerant kelp species, it is an ideal target for ocean farming and commercial cultivation, considering climate change.